Inflammatory Arthritis Induced by Pembrolizumab in a Patient With Head and Neck Squamous Cell Carcinoma - Spathas, Nikolaos; Economopoulou, Panagiota; Cheila, Myrto; Kotsantis, Ioannis; Fanouriakis, Antonis; Kassara, Dimitra; Psyrri, Amanda (Frontiers in Oncology, 2018)
Abstract INTRODUCTION : The use of Immunotherapy is shown to be effective in patients with head and neck squamous cell carcinoma (HNSCC) but also cause immune – related adverse events (irAEs). We report a case of inflammatory arthritis induced by pembrolizumab, a PD-1 inhibitor. CASE REPORT : A 55-year old male with stage IVB HNSCC was initially treated with concurrent cisplatin-based chemoradiotherapy. Sixteen months after diagnosis, the patients demonstrated lung metastases and started treatment with pembrolizumab 200mg iv every three weeks. After two cycles of immunotherapy, the patient presented with stiffness, swelling and pain of the right knee. Clinical examination and blood and synovial fluid analysis revealed a seronegative inflammatory arthritis. Pembrolizumab was hold and low-dose prednisone was given with remarkable clinical improvement. Pembrolizumab was reintroduced, but after the fifth cycle, symptoms appeared as inflammatory polyarthritis involving both knees and interphalangeal joints of both hands with important deterioration of the patient. At this time, we decided to permanently discontinue pembrolizumab treatment. After high-dose prednisone and methotrexate treatment the patient experienced significant remission of the symptoms. CONCLUSION : As our knowledge about rheumatic irAEs is limited and originates from case reports or case series, there is a need for further investigation to establish their clinical features. Surely, rheumatologic consultation is indispensable to manage such cases, especially the severe ones as this reported here.